ANALYSIS OF TEACHER'S ABILITY IN APPLYING MIKIR ELEMENTS IN ACTIVE LEARNING AT HIGH CLASSES IN THE PRIMARY SCHOOL - Yantoro (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research is to identify teachers’ ability in applying active learning with the elements of MIKIR (Experiencing, Interaction, Communication, and Reflection). This research used a descriptive qualitative approach. The research took place at Mendalo Elementary School 211/IX. The subjects of the research were high-class teachers (Class IV, V, and VI). Data were collected through observation, interviews, and documentation. The data were analyzed using data reduction techniques, data display, and data verification. The results showed that the high-class teachers had applied the elements of MIKIR in active learning. The ability of each teacher varied due to differences in vision and work ethic, the seriousness of the teacher in participating in active learning training applying the MIKIR elements, and the seriousness of the teacher in following up on the results of training and mentoring conducted by the principal. This study concluded that teachers have applied active learning using the MIKIR elements, but the quality of implementation must be improved in order to fully develop students’ potential.